Implementasi debat bahasa Inggris dengan metode British Parliamentary - Fatimah Hidayahni Amin; Indrawati Asfah; Seny Luchriani (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Debating is one of the communication activities which aims at conveying constructive, innovative, sistematic, andconvincing ideas and thoughts. One of the debating methods which can facilitate that aim is British Parliamentary. This debatingsystem uses English. British Parliamentary method consists of two opposite lines, government who agrees and supports themotion and opposition who disagrees and contradicts with the motion. In debating, there are four competing teams which argueagaints to win each other ideas and thoughts, they are: Opening government, Opening opposition, Closing government, andClosing opposition. Each team and speaker has their own respective rules and roles leading them to the systematic and structuredway of conveying ideas and thoughts. To debate using this method, students at Senior High School in Makassar have conducteddebating activities. The methods of the activties are introduction of rules and roles, case building, presentation, discussion,assignment, and debate exhibition. Based on these activities, it is indispensable to conduct a reguler and routine training in orderto reassure the students’ way of thinking analytically, systematically, and critically and to be more accustomed withcommunicating meaningfully in English.